An Adaptive Cross-Layer Architecture to Optimize QoS Provisioning in MANET - Asha Asha; G. Mahadevan (Institute of Advanced Engineering and Science, 2017)
Mobile Ad Hoc Network (MANET) is a collection of mobile nodes, which dynamically form a temporary network, without using any infrastructure like wireless access points or base-stations. The provision of QoS guarantees is much more challenging in Mobile Ad hoc Networks. There are many interesting applications such as multimedia services, disaster recovery etc can be supported if Quality-of-Service (QoS) support can be provided for MANETs. But QoS provisioning in MANETs is a very challenging problem when compared to wired IP networks. This is because of unpredictable node mobility, wireless multi-hop communication, contention for wireless channel access, limited battery power and range of mobile devices as well as the absence of a central coordination authority. So, the design of an efficient and reliable routing scheme providing QoS support for such applications is a difficult task. In this paper we studied the challenges and approaches for QoS aware routing techniques.